Opini Publik terhadap Pernyataan Presiden Prabowo tentang Proyek Whoosh: Analisis Sentimen Komentar YouTube Menggunakan Multinomial Naive Bayes dalam Perspektif Commentary Engagement - Dimas Adiz Setiawan; Dicky Andi Soffan; Harun Al Rosyid (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
YouTube plays a crucial role in shaping and expressing public opinion on national political issues. President Prabowo Subianto's statement regarding the Whoosh High-Speed ​​Rail project in the video "Tegas! Prabowo: Apa Itu Ribut-Ribut Whoosh, Saya Tanggung Tanggung" (Firm! Prabowo: Apa Itu Ribut-Ribut Whoosh, Saya Tanggung Tanggung) sparked a variety of responses in the comments section. This study aims to analyze public comment sentiment and its relationship to user engagement levels. The method used is sentiment analysis based on the Multinomial Naive Bayes algorithm with TF-IDF weighting, through text preprocessing and K-Fold Cross Validation (k = 2, 5, and 10) validation stages. The best results were obtained with the 10-fold scheme with an accuracy of 79.45%, a precision of 82.05%, and a recall of 79.45%. The sentiment distribution shows a dominance of neutral sentiment (59.41%), followed by negative (26.81%) and positive (13.78%), indicating a tendency for users to express opinions informatively and critically. The engagement level is relatively low with an average of 2.61 likes, 0.30 replies, and an engagement score of 0.0036. Correlation analysis shows that sentiment does not have a significant effect on engagement, so sentiment analysis is more appropriate for monitoring public opinion than predicting user engagement.